Development of a natural antifungal formulation for grated cheese and a microencapsulation approach using whey protein isolate and maltodextrin blend. Issue 9 (19th August 2022) - Sassi, Ghada; Salmieri, Stéphane; Allahdad, Zahra; Karboune, S.; Lacroix, Monique
Abstract: The antifungal activity of natural antimicrobials such as essential oils (EOs), citrus extracts, and other natural derivatives was evaluated against 10 fungal strains using minimum inhibitory concentration (MIC) analysis. Compounds having the highest inhibitory activity at the lowest concentrations were subsequently selected to evaluate the possible synergistic interactions by checkerboard method (FIC). The results showed that citrus extract A (CEA) and EOs rich in cinnamaldehyde had the highest inhibitory capacity against evaluated strains ( Aspergillus niger, Aspergillus versicolor, Aureobasidium pullulans, Eurotium rubrum, Paecilomyces spp., Penicillium chrysogenum, Penicillium citrinum, Penicillium commune, Penicillium crustosum, and Penicillium roqueforti ). The stability of the antifungal mixture was then optimized using lecithin and sucrose monopalmitate (SMP) as surfactants. Stability test showed that lecithin:SMP at HLB 10 maintains emulsion stability for 15 days of storage at 4°C. Encapsulation process for the loaded emulsion was optimized using whey protein isolate (WPI) and maltodextrin (MD) blend with ratios WPI:MD (1:2) and WPI:MD (1:3). The results showed that WPI:MD (1:3) led to a higher physicochemical stability (−40.5 mV), encapsulation efficiency (91%), and antifungal activity (315 ppm). Microencapsulation maintained the available active compounds content more prolonged with an average interval of 7 days compared to the nonencapsulated formulations during storage at 4°C.